As intimações do imaginário e a forma-ação do atorprofessor: cartas sobre a reeducação do sensível - Oliveira, Adriano Moraes de (2011)
This thesis describes how imaginary's intimations have influenced actorteachers' form-a(c)tion as structured and structuring structures: theater students, in an extracurricular perspective, were immersed in ten poetical experiments during almost three years in order to amplify their perceptions on imaginary's various intimations (symbolic groups of images) which take part in every moment of their and our lives. Is this amplification of the perception on the constant dislocations which everyone performs in the present (bersonian eternal duration) what configures a reeducation of the sensible? The answer to that question, originated from my research, is composed by a series of letters which intend to take the reader closer to the research trajectory itself. The "letters upon the reeducation of the sensible" highlight several movements; however, they reveal that the sensible is a dimension impossible to measure: one can try to have it measured, but that would mean potentizing the intelligible. For that reason, in the thesis report, the description and the direct speech were chosen as a sort of data analysis. The main references, which support the theoretical construct, are: studies on the imaginary (Gilbert Durand and Michel Maffesoli) and actor formation (Constantin Stanislavski and Jerzy Grotowski). With such references it was possible to observe the interaction between form (structured structure) and action (structuring structure), both interpellated and conformed by a complex texture of imaginary's intimations. That interaction, as a moving one, also allowed the juxtaposition of two different actants: the actor and the teacher, resulting in the actorteacher. The constant movement of students-researchers I denominate reeducation of the sensible, that is, the perception of the sharing which involves them with every part of life, including the underground ones.